Предмет: Математика,
автор: damirdosaliev00
Упростите выражение sin(a-pi/2)(cos(a-2pi)+2tg(3pi/2-a)sin(pi-a)cos(4pi+a)
Ответы
Автор ответа:
1
Ответ:
cos²α
Пошаговое объяснение:
sin(α-π/2)=sin(-(π/2-α))=-sin(π/2-α)=-cosα
cos(α-2π)=cosα
tg(3π/2-α)=sin(3π/2-α)/cos(3π/2-α)=-cosα/-sinα=cosα/sinα
sin(π-α)=sinα
cos(4π+α)=cosα
-cosα·cosα+2cosα·sinα·cosα/sinα=-cos²α+2cos²α=cos²α
Похожие вопросы
Предмет: Геометрия,
автор: Ydtixutxitd
Предмет: Математика,
автор: sofiakrasnova844
Предмет: Математика,
автор: vikaselivanova62
Предмет: Математика,
автор: sima071
Предмет: Алгебра,
автор: pyurtrqyet